2002
DOI: 10.1111/j.1432-2277.2002.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic interaction between portal vien and hepatic artery flow in small-for-size split liver transplantation

Abstract: In split-liver transplantation, the entire portal flow is redirected through relatively smallfor-size grafts. It has been postulated that excessive portal blood flow leads to graft injury. In order to elucidate the mechanisms of this injury, we studied the hemodynamic interactions between portal veinand hepatic artery flow in an experimental model in pigs. Six whole pig liver grafts were implanted in Group 1 (n = 6) and six whole liver grafts were split into right and left grafts and transplanted to Groups 2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 16 publications
3
67
0
1
Order By: Relevance
“…caused by associated suppression of the intrahepatic flow and thus less sinusoidal shear stress [7,19,32]. However, reduction in total hepatic inflow in simultaneously splenectomized and hepatectomized animals was marginal and not that pronounced what it would take to improve survival by reduced shear stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…caused by associated suppression of the intrahepatic flow and thus less sinusoidal shear stress [7,19,32]. However, reduction in total hepatic inflow in simultaneously splenectomized and hepatectomized animals was marginal and not that pronounced what it would take to improve survival by reduced shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of portal venous hyperperfusion in reduced-sizelivers, HABR may lead to hepatic arterial hypoperfusion [18,19]. For the reason that the regenerating liver requires an enormous amount of oxygen for its increased metabolic load and for DNA synthesis, suboptimal arterial inflow may be poorly tolerated in the reduced-size-liver and may increase the risk for organ dysfunction [20].…”
Section: Introductionmentioning
confidence: 99%
“…The first possible mechanism is that as the graft size in group S was smaller than in group N, it did not meet the demands of metabolism. SFS grafts have a relatively small liver mass because the GRBW is less than 0.8% and severe ischemic injuries caused by decreased hepatic arterial inflow or even hepatic artery thrombosis can occur [13][14][15] . Fukatsu et al [8] reported that graft hepatic weight was significantly correlated with clearance of tacrolimus in adult patients who had undergone LDLT, and Sugawara et al [16] reported that the optimal tacrolimus dose was best correlated with GV/SV ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Portal blood flow removes adenosine that has a local vasodilator effect on the arterial system [46,47] . However, an exaggerated HABR may contribute to ischemic injury in states of portal hyperfusion, as seen in small for size grafts [48,49] . Prophylactic splenic artery modulation [50,51] produced a significant reduction in portal flow causing a significant reduction in incidence of SFSS.…”
Section: Intraoperative Featuresmentioning
confidence: 99%